STUDIES ON THE UV-B RADIATION INDUCED OXIDATIVE DAMAGE IN THYLAKOID PHOTOFUNCTIONS AND ANALYSIS OF THE ROLE OF ANTIOXIDANT ENZYMES IN MAIZE PRIMARY LEAVES - K. SWARNA,; G. BHANUMATHI,; S. D. S. MURTHY, (The Bioscan, 2012)
In this study an attempt has been made to identify the targets for the action of UV-B radiation and possible protection mechanism in primary leaves of maize. UV- B radiation (2 – 8Wm-2) affected the photosystem II photochemistry (68% loss) and this inhibition is closely related to the extent of lipid peroxidation of thylakoid membranes. In addition there is an enhancement in the activities of antioxidant enzymes like superoxide dismutase, (76% increase) catalase (94% increases) which protects the thylakoid membrane from UV-B radiation induced oxidative damage.